Hubungan Anemia pada Ibu Ketika Hamil dengan Kejadian Stunting pada Balita di Daerah Lokus Stunting Kabupaten Lombok Utara - Suryantini, Ni Kadek Mega; Nurbaiti, Lina; Parwata, Wayan Sulaksmana Sandhi (Universitas Udayana, 2024)
Stunting in toddlers is a global problem. Stunting can arise because of different factors associated with the growth and development process and chronic malnutrition within the long time that takes place for the duration of the 1.000 First Days of Life (HPK). Stunted toddlers have a lower length or height when compared to their peers and result in non-optimal development of cognitive, motor, and verbal. This observe to decide the connection among anemia in mothers while pregnant with the occurrence of stunting in toddlers withinside the stunting locus location of North Lombok Regency. This studies with a type of analytical design with a cross-sectional approach. The subjects of the study were mothers who had toddlers aged 0-24 months totaling 106 respondents in the Stunting Locus of North Lombok Regency which was carried out using stratified random sampling techniques. Data collection obtained from the Maternal and Child Health book (KIA) and a questionnaire with bivariate data analysis using the chi square test. The consequences confirmed that there were 28.3% of mothers who experienced anemia while pregnant and 50.9% of stunting toddlers in the Stunting Locus of North Lombok Regency. The results of the bivariate test using the chi-square method obtained a p value of 0.459 (p>0.05) which confirmed that there was no significant relationship among anemia in mothers while pregnant and the occurrence of stunting in toddlers withinside the stunting locus of North Lombok Regency.